A "Soil Lorax" Perspective on Corn Stover for Advanced Biofuels. (1st January 2019) - M‐F Johnson, Jane
Abstract : Core Ideas: Corn stover is a potentail feedstock for advanced biofuels. Benefits and risks assoicated with harvesting residues reviewed. Strategies to protect soil if residues harvested summarized. Crop residues like corn ( Zea mays L) stover are potential feedstock for production of advanced biofuels (e.g., cellulosic ethanol). Utilization of residue like stover for biofuel feedstock may provide economic and greenhouse gas mitigation benefits; however, harvesting these materials must be done in a manner that protects the soil. This paper summarizes an introductory overview presented at the American Society of Agronomy (ASA), Crop Science Society of America (CSSA), and Soil Science Society of America (SSSA) workshop in Sacramento, CA, on crop residue removal for advanced biofuel production. Corn stover has been identified as an advanced biofuel feedstock, which could provide agronomic, economic and greenhouse gas mitigation benefits. However, stover harvest may result in soil exposed to erosive forces, and inadequate residue input for sustaining soil organic matter, resulting in soil degradation and other negative environmental consequences. Thus, strategies to protect the soil resource to balance current and future societal needs are required. Returning adequate residue and/or adding cover crops can mitigate or reduce risks to soil properties, which may be adversely impacted by harvesting crop residue. It is paramount to safeguard the soil so this indispensable resource continues providing a wide range of services including feeding and clothing a growing population.